Analisis Strategi Penyaluran Dana Zis Pada Lembaga Amil Zakat Dompet Dhuafa Republika - Annisa Aulia Machmudah; Chaidir Iswanaji (STIS DAFA MATARAM, 2021)
The purpose of this study to determine how the strategy used by Dompet Dhuafa Republika in distributing ZIS funds to the community. The method used descriptive qualitative with reference to scientific works and other sources relevant to the object of this research. Dompet Dhuafa as an amil zakat institution has a strategy in distributing ZIS funds. The results of this study indicate that Dompet Dhuafa's strategy in distributing ZIS funds can be said to be quite effective. The distribution of ZIS funds is not only in the form of real assistance, but also in the form of empowerment through various programs and skills training for beneficiaries